6. EVALUASI KINERJA KPK ERA KEPEMIMPINAN SUSILO BAMBANG YUDHOYONO - Adhi, Suwanto (FORUM, 2007)
Combatting corruption comission (KPK) is established to enfore law and democracy. This commission need strong trusts, not only from political elites, but also from all Indonesian people. The strategy to combat corruption is trully not only dependent on formal independent institution (like KPK), but also need supports from all Indonesian society.